2011
DOI: 10.1128/jcm.00908-11
|View full text |Cite
|
Sign up to set email alerts
|

High Concordance between the Position-Specific Scoring Matrix and Geno2pheno Algorithms for Genotypic Interpretation of HIV-1 Tropism: V3 Length as the Major Cause of Disagreement

Abstract: The agreement between the position-specific scoring matrix (PSSM) and geno2pheno as tools for genotypic interpretation of HIV-1 tropism using 800 clinical specimens was assessed. There was an overall concordance of 88%. Disagreement was found mostly in specimens with short V3 lengths (<35 amino acids). Thus, consideration of V3 lengths should improve the predictability of HIV-1 tropism using genotypic algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
3
13
2
Order By: Relevance
“…In parallel, the same patients were analyzed with the TrofileES test. Previous studies have confirmed the good agreement between the phenotypic format of TrofileES and the genotyping tool Geno2Pheno on a retrospective comparison of a large study population in clinical studies (47,48). As further confirmation, we also performed a parallel analysis with TrofileES on a limited set of 20 clinical samples.…”
Section: Resultssupporting
confidence: 50%
“…In parallel, the same patients were analyzed with the TrofileES test. Previous studies have confirmed the good agreement between the phenotypic format of TrofileES and the genotyping tool Geno2Pheno on a retrospective comparison of a large study population in clinical studies (47,48). As further confirmation, we also performed a parallel analysis with TrofileES on a limited set of 20 clinical samples.…”
Section: Resultssupporting
confidence: 50%
“…In general, population-based sequencing tests are less sensitive and less specific than phenotypic assays (14,29), although a few studies have shown significant concordance and similar predictive values (40,68,69). On the other hand, more sensitive deep sequencing methods for HIV-1 coreceptor tropism assays resulted in the detection of minor variants, which correlated well with both phenotypic assays (39,40,57) and virological response to maraviroc (39,40).…”
Section: Discussionmentioning
confidence: 71%
“…49 We found that 18% (56/304) of samples had a V3 loop length that was not the standard 35 codons ( s105 nucleotides; Table 1) and 53/56 (95%) V3 loops had a single-codon deletion and a length of 102 nucleotides. Of V3 loop length variants 7/56 (12%) and 11/56 (20%) were classified as non-R5 by ESTA and UDS, respectively, compared to …”
Section: V3 Loop Length Variationmentioning
confidence: 72%